Fentanyl for labour pain management: a scoping review - Kyaw Lwin Show; Chetta Ngamjarus; Kiattisak Kongwattanakul; Siwanon Rattanakanokchai; Chatuporn Duangkum; Meghan A. Bohren; Ana Pilar Betrán; Monsicha Somjit; Wint Ye Hla Win; Pisake Lumbiganon (BMC, 2022)
Abstract Background Labour pain has been identified as an important reason for women to prefer caesarean section (CS). Fentanyl is one of the short acting opioids recommended by World Health Organization for pain relief during labour. This study aimed to identify and describe the available evidence on the use of fentanyl (monotherapy) for labour pain management by any routes of administration or regime. Methods We included the records published until 31 December 2021 which reported administration of fentanyl to women with normal labour for labour pain relief. Data were extracted by one reviewer and checked by another reviewer using a standardised agreement form. We mapped and presented data descriptively in figure and tabular format. Results We included 51 records from 49 studies in our scoping review. The studies were conducted in 12 countries, mostly high-income countries. The study designs of the 51 included records were varied as follows: 38 (74.5%) experimental studies (35 randomised controlled trials and three quasi-experimental studies), and 12 (23.5%) observational studies (five retrospective cohort studies, four prospective cohort studies, two retrospective descriptive studies, and one descriptive study) and one qualitative study. Of the included records, six used intranasal fentanyl, five used subcutaneous fentanyl, 18 (35.3%) used intravenous fentanyl, 18 (35.3%) used intrathecal fentanyl, and nine used epidural fentanyl. Many records compared fentanyl with another analgesic agent while five records (9.8%) had no comparison group and seven records (13.7%) compared with no analgesia group. The doses of fentanyl varied by routes, study and the requirement depended on the women. Pain assessment was the most frequent outcome measure presented in the records (78.4%). Only nine records (17.6%) investigated women's satisfaction about labour pain relief using fentanyl and seven records (13.7%) reported the effect of fentanyl on breastfeeding. The most common reported neonatal outcomes were foetal heart rate (33 records, 64.7%) and Apgar score (32 records, 62.7%). Conclusion There is limited primary evidence especially randomised controlled trials to evaluate the effectiveness and harms of different routes of fentanyl in low- or middle-income countries. There is a need for high-quality research to establish the most effective route of fentanyl and associated effects for evidence-based international guidelines.